Rural institutions and imperfect agricultural markets in Africa: Experiences from producer marketing groups in Kenya - Shiferaw, Bekele; Muricho, Geoffrey; Kassie, Menale; Obare, Gideon (University of Pennsylvania Press, 2011)
The analysis and evidence presented here have shown that farmers selling to PMGs receive higher prices than otherwise, opening new opportunities for smallholder farmers to benefit from markets. Although the marketing channels in the study areas are characterized by long and complex chains and high transaction costs, which considerably lower the farmers' share of the consumer prices, PMGs improved market access for small producers by bulking, storage, grading, sorting, and selling the produce directly to buyers at the upper end of the value chain. The links to secondary and tertiary markets were enhanced through better coordination of production and marketing activities. There is no evidence that the PMGs benefited only the wealthier, resource-rich farmers. On the contrary, the incentive for joining collective marketing groups seems to be higher for those with smaller farmlands, but not necessarily for the poorest.